2006
DOI: 10.1172/jci26523
|View full text |Cite
|
Sign up to set email alerts
|

Leptin neutralization interferes with pathogenic T cell autoreactivity in autoimmune encephalomyelitis

Abstract: Recent evidence has indicated that leptin, an adipocyte-secreted hormone belonging to the helical cytokine family, significantly influences immune and autoimmune responses. We investigate here the mechanisms by which in vivo abrogation of leptin effects protects SJL/J mice from proteolipid protein peptide PLP 139-151 -induced EAE, an animal model of MS. Blockade of leptin with anti-leptin Abs or with a soluble mouse leptin receptor chimera (ObR:Fc), either before or after onset of EAE, improved clinical score,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 29 publications
0
96
0
3
Order By: Relevance
“…Abnormalities in the immune system have been reported in db/db mice, which suggests that the immune system might be involved in the pathogenesis of diabetes [29,30]. Recent studies have shown that leptin-deficient ob/ob mice are resistant to induction of experimental autoimmune encephalomyelitis, and leptin blockade inhibits T cell autoreactivity and slows disease progression in SJL/J mice [31,32]. Thus, further studies on DC function in db/db mice may provide new insights into our understanding of whether and to what extent DC contribute to the pathogenesis of diabetes development.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the immune system have been reported in db/db mice, which suggests that the immune system might be involved in the pathogenesis of diabetes [29,30]. Recent studies have shown that leptin-deficient ob/ob mice are resistant to induction of experimental autoimmune encephalomyelitis, and leptin blockade inhibits T cell autoreactivity and slows disease progression in SJL/J mice [31,32]. Thus, further studies on DC function in db/db mice may provide new insights into our understanding of whether and to what extent DC contribute to the pathogenesis of diabetes development.…”
Section: Discussionmentioning
confidence: 99%
“…Male C57BL/6j mice (5-weeks old) ( Janvier Labs, St. Berthevin, France) were divided in six groups: two control groups that were untreated and exposed to normoxia or hypoxia; two groups treated with daily intraperitoneal injections of recombinant Ob from day −2 to day 21 (3 μg·g −1 of initial body weight [18]), exposed to normoxia or hypoxia; two groups treated with daily i.p. injections of soluble [19]), exposed to normoxia or chronic hypoxia. Sprague-Dawley male rats (4-weeks old) (Charles River Laboratories, Larberesle, France) were divided into four groups: two control groups (vehicle in drinking water) exposed to normoxia or hypoxia; two groups treated with DCA from day 14 to day 21 (1 g·L −1 in drinking water) exposed to normoxia or chronic hypoxia.…”
Section: Animal Models and Haemodynamic Measurementsmentioning
confidence: 99%
“…An example of the first approach is a recombinant human and mouse Ob-R/Fc chimeric glycoprotein. 171,172 Only the latter 2 approaches have been employed in cardiac-related research. In neonatal rat ventricular cardiomyocytes, rat L39A/D40A/F41A leptin mutein blocked hypertrophic effects and abolished increases in Ob-R gene expression elicited by leptin, Ang II, or ET-1.…”
Section: Leptin Antagonistsmentioning
confidence: 99%